Redesain Taman tegar Beriman Cibinong dengan Pendekatan Elemen Lanskap Ramah Pandemi Pada Pasca Kenormalan Baru - Retnogumi, Yudyastri; hadi, akhmad arifin (Prodi Arsitektur Universitas Matana, 2025)
The global spread of Covid-19 in Indonesia has posed severe challenges. The government has implemented access restriction policies to prevent the spread of the virus. While beneficial in the context of health, these policies have negatively impacted individuals' physical and mental well-being, as humans inherently require open spaces for tranquility, contemplation, and others. However, many city parks have been abandoned during the pandemic due to a lack of supporting facilities, including Taman Tegar Beriman. Given these conditions, this research aims to redesign Taman Tegar Beriman using a pandemic-friendly landscape approach incorporating the new normal concept. Spatial and descriptive analysis methods are employed to process physical, biophysical, and health data and identify community preferences. The design stages include analysis, schematic concepts, site plans, and construction drawings. The fundamental concept of this redesign is to optimize the function of Taman Tegar Beriman as a city park that is safe from the risk of virus transmission. The design concept draws inspiration from the radial and linear forms of the virus, which are then applied to the spatial layout, circulation, and facilities within the park. The design results can be a reference in rebuilding Tegar Beriman Park, which can adapt to future pandemic conditions.